First report of Pineapple mealybug wilt-associated virus 1 and 3 associated with mealybug wilt of pineapple disease on pineapple in Malaysia - Mohd Anuar, I.S.; Nusaibah, S.A.; Vadamalai, G.; Mokhtar, A.S.; Sapak, Z (John Wiley & Sons, 2023)
Mealybug wilt of pineapple (MWP) disease could be a limiting factor for pineapple (Ananas comosus) production worldwide. Pineapple mealybug wilt associated viruses (PMWaVs) have been established as the causative agent of MWP in Cuba and Peru (Hern¡ndez-Rodr±guez et al. 2019; Carrasco-Lozano et al. 2023), the viruses being vectored by mealybugs (Sether et al. 2005). The characteristic symptoms of MWP are chlorotic patches along the lamina with necrotic leaf tips (Carrasco-Lozano et al. 2023). In July 2022, leaf samples of pineapple cv. MD2 with typical MWP symptoms were collected from farms in Melaka (ten samples) and Johor (ten samples) (Figs. 1-2). Total RNA was extracted from the samples using an RNeasy Plant Mini Kit (Qiagen, The Netherlands) following the manufacturers instructions and tested by three PCR assays that target the heat shock protein 70h (HSP70h) gene of PMWaV-1 (primers PMWaV-1-225/PMWaV-1-226; Sether et al. 2005), PMWaV-2 (primers PMWaV-2-223/PMWaV-2-224; Gambley et al. 2008; Sether et al. 2005) and PMWaV-3 (primers PMWaV-3- 263/PMWaV-3-264; Sether et al. 2005). PCR amplicons of the expected size were observed for PMWaV-1 (600 bp) in all ten samples from Melaka, for PMWaV-2 (600bp) in five samples from Johor and for PMWaV-3 (500 bp) in the other five samples from Johor. The PCR products were sequenced and the sequences analysed and compared to sequences in GenBank using BLASTn. The sequences from the ten PMWaV-1 isolates (GenBank Accession Nos. OP684934, OP746058-060 and OQ641698-703) had 99-100 nt identity to PMWaV-1 isolates from Thailand (HE583225) and Cuba (HQ129930). The sequences of the five PMWaV-2 isolates (OQ672485-489) had 99-100 nt identity with two PMWaV-2 isolates from Cuba (JX508637 and JX645772). The sequences of the five PMWaV-3 isolates (OQ672490-494) had 99.4 nt identity with isolates from Taiwan (FJ209047) and Cuba (GU563497). The samples were tested in three PCR assays using primers PMaV-1-FJ08-1/ PMWaV-1-FJ08-2 (Shen et al. 2009), PMaV-2-CP229/PMaV-2-CP230 (Hernandez-Rodriguez et al. 2014) and PMWaV-3- CP231:/PMWaV-3-CP232 (Hernandez-Rodriguez et al. 2014), which target the coat protein (CP) genes of PMWaV-1, -2, and -3 respectively. The amplicons were sequenced and BLASTn analysis confirmed the presence of each virus in the pineapple samples, supporting the initial findings. The CP sequences of the ten PMWaV-1 isolates (OQ672495-504) had 99.2-99.4 nt identity with isolates from Cuba (JN995531 and JN995532), the sequences of the five PMWaV-2 isolates (OQ700918- 922) had 99.1-99.7 nt identity with isolates from Hawaii (MH704741 and OP860299) and the sequences of the five PMWaV-3 isolates (OQ700923- 927) had 98.9-99.9 nt identity with isolates from Hawaii (MT990953 and MN539274). Mealybug wilt of pineapple is widely spread in Malaysian pineapple farms. PMWaV-2 was known to occur in MWP-affected cvs. Gandul and Mauritius in Johor Malaysia (Sether et al. 2001). To our knowledge, this is the first report of PMWaV-1 and -3 in pineapple in Malaysia. Pineapple is a vegetatively propagated crop and PMWaVs could become prevalent in pineapple farms via the distribution of virus-infected suckers. Therefore, pineapple farmers need to be educated and trained in good management practices when propagating pineapple materials from disease-free sources to prevent and/or control the spread of the MWP in Malaysia.